Restrukturisasi proses berpikir pseudo dalam memecahkan masalah matematika ditinjau dari gaya kognitif reflektif dan impulsif - Riyantika, Era; Muniri, Muniri; Maryono, Maryono (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2023)
Many students assume that they have carried out the correct thinking process in solving problems, but in reality students only imitate the procedures carried out by the teacher without understanding mathematical concepts. This condition is called pseudo thinking. Errors in the structure of thinking can be solved by rearranging the wrong thought process, namely restructuring the thought process. This research uses a qualitative approach with the type of case study research conducted at class VIII SMPN 1 Sumbergempol. The subjects of the study consisted of 4 students divided into 2 impulsive cognitive style subjects and 2 reflective subjects. Selection of research subjects using purposive sampling techniques. Data collection techniques used were MFFT tests, problem solving tests, and interviews. Data analysis used the Spiral model with results 1) Fragmentation experienced by impulsive students, namely fragmentation of pseudo-incorrect thinking. 2) The fragmentation experienced by reflective students, namely the fragmentation of pseudo-true. 3) The application of restructuring to impulsive students who experience pseudo-wrong thinking can provide a complete structuring of thinking, so that students can solve problems in a structured and correct manner. 4) The application of restructuring to reflective students who experience pseudo-corruption can really provide a complete structuring of thinking, so that students can have the right mindset.